A Production Systems Study on Veg Oil - Ayeng, Juan Carlos G. (College of Engineering, 1996)
The company under study, Veg Oil, is a refinery located at E. Rodriguez, Libis. They refine crude palm oil and produce cooking oil. Their products include soap, shortening, palm kernel (pk) meal, (pk) palm kernel oil and hydrogenated flakes. The study is concentrated on the milling operations which transforms palm kernel into palm kernel meal and palm kernel oil. Forecasting, capacity, and aggregate planning were done as a basis and guide for production plans and recommendations. There exists a problem of poor production scheduling which results in work stoppages. This is due to the limiting constraints of lack of storage space and low demand for pk meal. Since the demand for pk meal and pk oil are different, satisfying the demand for one product leaves either a shortage or an abundance of the other product. Currently, to avoid an overabundance of pk meal, the company is operating to meet pk meal demand only and the shortage of pk oil is satisfied by buying it from an outside supplier. However, based on forecasts, it has been determined that from June to August, there will be an abundance of pk oil. This does not bode well for the company because excess pk oil has to be disposed. This entails additional costs which are very large. To combat this problem, different production schedules were determined and evaluated according to the following criteria: 1. Continuity of production (40%) 22. Minimization of waste (30%) 3. Cost effectiveness (30%). The alternative that was chosen was the one the plans to vary production planningby satisfying pk oil needs a few months before the pk oil demand dips below the pk meal demand and stocking the excess meal produced. This is because during the months wherein pk oil dips below pk meal demand, the excess meal inventoried can be used to satisfy pk meal demand. A second problem, that of excess materials handling, was also evaluated. A new materials transport system was compared to the old method of shipping the palm kernels by sack through a shipping line. The new method consists of shipping pk in bins through barges owned By Veg. Oil. This method effectively reduces costs and lead time in transportation. Also, to supplement this new transportation system, an MRP-type of inventory system was set up and a corresponding schedule was produced. Furthermore, it was suggested the the feasibility of putting up a warehouse within the plant compound be studied, as well as looking into expanding the pk meal market.